Local Institutions Performance in Mangrove Forest Management on Small Islands: Case Study in Buano Island, Maluku Province, Indonesia - Salampessy, Messalina Lovenia; Nugroho, Bramasto; Kartodiharjo, Hariadi; Kusmana, Cecep (Jurnal Sylva Lestari, 2024)
Mangrove forests on small islands play an essential role in the stability of island ecosystems. It is crucial to analyze the performance of local institutions in forest management to increase the community’s active role in preserving mangrove forests. This research aims to analyze the performance of local institutions managing mangroves on small islands. The research was conducted on Buano Island, Maluku, Indonesia. In-depth interviews and participant observation were used to obtain data. Data analysis uses a Situation, Structure, Behavior, and Performance (SSBP) approach. The research results show that the community is very dependent on mangrove forests. Resources are owned by the clan group (Soa) but managed by members of the clan group (family). Thus, the phenomenon occurs when common pool resources are managed by private (Dati/Nuru) proprietors. The community regulates the utilization of potential forest resources by dividing management areas controlled by each Soa/Nuru group. The preservation of natural potential on Buano Island is supervised by Kewang and Sasi culture. Applying customary rules increases the community’s active role in managing resources and supporting village management. However, mangrove forest logging activities continue to occur. This performance shows a very high decline in mangrove forest vegetation and regeneration of mangrove forests. Stakeholder support is needed to increase the knowledge and skills of the community, especially traditional leaders, in implementing sustainable forest management. Keywords: forest management, local institution, mangrove, small island